PENGARUH KINERJA PENAMBAHAN KARET BAN BEKAS SEBAGAI SUBSTITUSI PENGGANTI CAMPURAN BERASPAL DAUR ULANG PADA LAPIS PERMUKAAN ATAS - DARMA PRABUDI; KOSIM KOSIM (Politeknik Negeri Sriwijaya, 2015)
Method of pavement recycling is an alternative technology in pavement construction and maintenance of roads that allow the use of wastes produced by the old pavement. Therefore, researchers tried using the method of recycling by using old materials and reprocessed by adding a fluxing materials and ingredients added in the form of powder rubber tires. This research aims to restore the value of the power of the old pavement. The beginning stage of this study seek additional level of asphalt most optimal mix of recycling based on the value of maximum stability, obtained the addition of optimum bitumen content is 1%. Then, the addition of tire rubber powder ranging from 10%; 20%; 30%; 40% and 50% by replacing most of the asphalt with rubber powder tire to the addition of the most optimum bitumen content. The highest stability values that are in a mixture of 10% levels of tire rubber powder to the optimum bitumen content is 4657.3 kg, while the value of flow at a level of 10% of tire rubber powder that is 3.32mm. The increasing levels of tire rubber powder in the mix, then the Marshall Quotient value decreases, the value of the highest Quotient marshall is on the addition of tire rubber powder content of 10% of additions optimum bitumen content is 1402.8 kg / mm. Highest Density Values are at the addition of tire rubber powder content of 10% of additions optimum bitumen content of 2.300 gr / cm3. Of all the parameters indicate the presence of tire rubber powder in the mixture can increase the value of the power and flexibility of pavement.